Catfishing, Is it Unregulated Crime in Indonesia? - Shaqilla, Nikita; Reda, Yahia (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2024)
Catfishing is a type of an international cybercrime. Unfortunately, it lacks clarity in Indonesia’s national framework. Catfishing, which utilizes a fake identities on the internet, can be classified as fraud. This study examines the legal consequences in personal relationships stemming from the practice of online fraud. This study used a normative juridical approach with empirical data, this study raises the questions of why teenagers engage in catfishing on social media and explains the legal complexities it entails. As a result, this research shows that 99 percent of respondents - teenagers inside and outside North Sumatra Province - lack self-awareness about catfishing issues in building online relationships. This type of fraud is often committed when registered on social media, even though this can be an entry point for catfishing and subsequent legal offenses, especially fraud as regulated in Article 378 of the Criminal Code